PRODUCTIVITY AND GRAIN QUALITY OF WINTER WHEAT DEPENDING ON NITRIC TOP-DRESSINGS AFTER SUMMER BARLEY - Ноздріна, Н. Л. (Scientific Progress & Innovations, 2015)
The productivity and quality of grain (nature, content of protein and gluten, index of gluten deformation) of new varieties of winter wheat after barley summer are considered. It was established, that the greatest productivity of all varieties had been received in favorable on moistening 2013 and 2014 years, smaller – in droughty 2012 year. The influence of nitric top-dressing on formation of indicators of productivity and quality of grain of winter wheat was established. The greatest content of protein and gluten in grain was marked at variety Sonechko and in a variant, in which combined the application of ammonium nitrate early in the spring on thawed frozen ground and at the end of tillering stage locally.